2007
DOI: 10.1111/j.1432-2277.2006.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of recurrent focal segmental glomerulosclerosis after kidney transplantation by plasmapheresis and rituximab

Abstract: A 22-year-old patient whose primary kidney disease was focal segmental glomerulosclerosis (FSGS) developed severe recurrence of proteinuria (up to 57 g/24 h) immediately after a haploidentic living donor kidney transplantation despite pre-operative plasmapheresis. The immunosuppressive treatment consisted of tacrolimus, mycophenolate mofetil, basiliximab and steroids. He underwent 10 plasmapheresis sessions in the first 3-week post-transplantation. In addition, he received 2 i.v. doses of rituximab (RTX) 600 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 28 publications
2
69
0
4
Order By: Relevance
“…Since the year 2000, numerous case reports and small studies of the efficacy of rituximab in treating FSGS have been published [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. The larger case series are summarized in Table 3.…”
Section: Treatmentmentioning
confidence: 99%
“…Since the year 2000, numerous case reports and small studies of the efficacy of rituximab in treating FSGS have been published [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. The larger case series are summarized in Table 3.…”
Section: Treatmentmentioning
confidence: 99%
“…Some case reports have suggested that rituximab could be effective to resolve recurrent nephrotic syndrome after renal transplantation in patients whose primary renal disease was FSGS (5)(6)(7)(8)(9). The potential usefulness of rituximab has also been explored in patients with steroid-dependent or steroid-resistant forms of nephrotic syndrome.…”
mentioning
confidence: 99%
“…5,6,[13][14][15] If such an aggressive disease recurs after transplant, a poor prognosis should be expected and alternative treatments considered as soon as a formal diagnosis is available. 5,6,10,[13][14][15][16][17][18] Our study was retrospective in nature and had a relatively small sample size. However, the cohort of patients was overall homogeneous, data were prospectively collected by qualified personnel, and the follow-up was extended enough to allow proper evaluation of long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%